The Role of Social Media Use in Shaping Trust and Purchase Intention for Generative AI Technologies - Prahasta, Luqman Rabbani; Fikriah, Nur Laili; Afifah, Yans Nur (IQTISHODUNA, 2025)
This research investigates the role of social media use in shaping trust and purchase intention for Generative AI (GenAI) technologies among university students. Utilizing a quantitative approach with primary data collected through questionnaires from 160 students in Malang, Indonesia, this study employs Partial Least Squares Path Modeling (PLS-PM) for data analysis. The results indicate that sociability, usability, dependency, and involvement in social media significantly influence social media usage. Social media usage, in turn, significantly impacts both trust in GenAI and, to a lesser extent, purchase intention. Moreover, trust has a strong positive effect on purchase intention. Importantly, the study confirms that trust mediates the relationship between social media use and purchase intention. These findings highlight the crucial role of social media in shaping consumer behavior and the significance of trust in promoting adoption of new technologies like GenAI.